KEPAILITAN SEBAGAI INSTRUMEN PENGEMBALIAN KEKAYAAN: STUDI LITERATUR TERHADAP HUKUM KEPAILITAN DI INDONESIA - Faizul Idris; Ashuri Ashuri; Edi Mulyadi (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Bankruptcy is a legal instrument designed to collectively resolve debt disputes through a mechanism for managing and liquidating the assets of bankrupt debtors. Normatively, bankruptcy law in Indonesia aims to ensure the return of bankrupt debtors' assets to creditors in a fair, proportional, and legal manner. However, in practice, the effectiveness of bankruptcy as an asset recovery instrument still faces various obstacles. This study aims to analyze bankruptcy as an asset recovery instrument from the perspective of bankruptcy law in Indonesia and identify gaps between normative objectives and its implementation in practice. This study uses a normative legal research method with a literature review approach, through an examination of relevant laws and regulations, legal doctrine, and previous research findings. The results indicate that although bankruptcy law has a comprehensive normative framework, the effectiveness of asset recovery in bankrupt debtors is still hampered by legal and non-legal factors, such as asset complexity, limited asset tracing, curator professionalism, and inconsistent judicial practices. Therefore, strengthening the implementation of bankruptcy law is necessary so that it can function optimally as a creditor protection instrument and support a healthy business climate.